ANALYSIS OF FACTORS INFLUENCING FINANCIAL PERFORMANCE OF FOOD AND BEVERAGE COMPANIES LISTED ON THE IDX IN 2022-2024 - Restauli Simarmata; Iskandar Muda; Abdillah Arif Nasution (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study investigates the factors influencing financial performance in food and beverage companies listed on the Indonesia Stock Exchange (IDX) during 2022–2024. As the food and beverage sub-sector plays a pivotal role in economic development and contributes significantly to Indonesia’s GDP and export value, understanding the financial determinants is crucial. Using agency theory as a framework, this research analyzes the impact of four financial ratios Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TAT), and Net Profit Margin (NPM) face off Return on Assets (ROA). The study applies a quantitative approach with panel data regression and utilizes secondary data from annual reports of 71 food and beverage companies over three years. Fixed Effect Model (FEM) was selected as the best fit based on Chow and Hausman tests. The results reveal that DER and NPM significantly affect ROA, where DER negatively impacts financial performance, while NPM has a strong positive influence. In contrast, CR and TAT do not exhibit statistically significant effects on ROA. These findings suggest that capital structure and profitability management play essential roles in enhancing corporate performance, while liquidity and asset utilization require further strategic alignment to improve outcomes in this sector.